Numerical study on the elastic buckling of cross-laminated timber walls subject to compression - Pina, Juan Carlos; Saavedra Flores, Erick I.; Saavedra, Karin (Construction & building materials, 2019)
•A multiscale model is adopted to compute the buckling capacity of CLT walls.•The homogenization is sequentially carried out from nano to structural scale.•Experimental tests are conducted to determine buckling critical load of CLT walls.•The influence of openings on CLT wall buckling capacity is investigated. The recent trend towards the use of Cross-Laminated Timber (CLT) as a novel construction material in mid- and high-rise buildings has steered the research efforts into this subject over the last few years. Despite the considerable progress made on the structural response of CLT, there are still several unresolved issues related to the analysis and design of CLT. This is of great interest for engineers and designers working on the mass timber construction sector. In particular, the buckling behaviour of CLT walls is a problem not fully understood to date. Therefore, in this paper we investigate the buckling capacity of CLT subject to compressive loads. In order to capture the heterogeneities present in wood, a multi-scale modelling strategy is adopted. To improve the numerical predictions, an optimisation-based parameter identification procedure is performed to calibrate the micromechanical parameters of wood. The numerical predictions are compared with experimental results and are validated successfully. The numerical model is then used to study the influence of the number of layers and wall openings on the buckling capacity of CLT walls.